B-19. What does eye tracking tell us about neurological patients?. Issue 5 (May 2018) - Terao, Yasuo; Matsumoto, Hideyuki; Matsuda, Shun-ichi; Tokushige, Shin-ichi; Inomata-Terada, Satomi; Hamada, Masashi; Hanajima, Ritsuko; Ugawa, Yoshikazu
Abstract : Performances of experimental oculomotor (saccade) paradigms have provided insights into the pathophysiology of neurological patients. However, to investigate the behavioral correlates and the physiological significance of these saccade abnormalities in daily life, we need to look into the difficulty patients actually experience in a more ecological setting. We review studies in which the eye tracking methodology was applied to normal subjects, e.g., when they viewed line drawings presented on a monitor screen to memorize them for later recall. In addition, simultaneous recording of hand (finger) movements with gaze movements allows us to evaluate how the eye and hand coordinates in performing daily actions. For example, eye-hand coordination was studied whey subjects wrote letters on a touch panel, and during a trail making test or in a task simulating finger-nose test. Even eye-voice coordination can be studied by recording the voice of subjects as they read aloud a text. Investigations in neurological patients such as Parkinson's disease and cerebellar ataxia holds promise for giving insights into how saccade abnormalities observed in oculomotor tasks contribute to their clinical symptoms. They can also be used to quantitatively evaluate motor symptoms of neurological patients from a new perspective.